ANALISIS BIAYA VOLUME LABA SEBAGAI ALAT PERENCANAAN LABA (SPBU CV. SINAR HASMADANI) - Aina Mustainah, Suci Ayu (Bongaya Journal of Research in Accounting (BJRA), 2019)
This study aims to determine the costs incurred whether it has reached breakeven by SPBU CV. Sinar Hasmadani, how much sales volume is spent to break even andto find out the profit generated has become a reference in planning future profits at gasstations CV. Sinar Hasmadani Karsa. This study uses primary data and secondary data,where primary data is obtained from companies related to the history of the company.Secondary data in this study in the form of financial report data and data costs that existwithin the company. In this study the method used to analyze the data is by usingquantitative descriptive.The results of the analysis show that the costs incurred by SPBUCV. Sinar Hasmadani Karsa can be used as a basis for calculating BEP. Sales volumealso increases every year, on the other hand the calculation of contribution margin andcontribution margin ratio obtained in 2016-2018 shows that the company has produced acontribution margin that can cover fixed costs and generate maximum profits, and thelast profit achieved by the company can be used as the basis for future profit planning